2019
DOI: 10.1111/jgs.16231
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer‐Measured Hospital Physical Activity and Hospital‐Acquired Disability in Older Adults

Abstract: BACKGROUND: Hospital-acquired disability (HAD) is common and often related to low physical activity while in the hospital. OBJECTIVE: To examine whether wearable hospital activity trackers can be used to predict HAD. DESIGN: A prospective observational study between January 2016 and March 2017. SETTING: An academic medical center. PARTICIPANTS: Community-dwelling older adults, aged 60 years or older, enrolled within 24 hours of admission to general medicine (n = 46). MAIN MEASURES: Primary outcome was HAD, def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 30 publications
(54 reference statements)
4
69
0
Order By: Relevance
“…When hospitalised with an acute medical illness, older adults are at high risk of functional decline, newly acquired disabilities and poor outcomes that persist post-hospitalisation such as continued decline, institutionalisation and death [13][14][15]. Research is only beginning to investigate activity dosage in older medical patients with reports of: a reduced risk of 30-day hospital readmission above a threshold of 275 steps per day and further risk reduction for every 100 step increase in mean daily steps [16]; an increased risk of hospital associated functional decline if taking ≤900 steps per day [17,18] and the suggestion that walking at least twice a day for 20 min is associated with less functional decline in people of variable physical capabilities [19]. The problems of low mobility and SB in hospitals are complex because there are system issues, in addition to challenges relating to people, culture, the environment and operational processes [20].…”
Section: Introductionmentioning
confidence: 99%
“…When hospitalised with an acute medical illness, older adults are at high risk of functional decline, newly acquired disabilities and poor outcomes that persist post-hospitalisation such as continued decline, institutionalisation and death [13][14][15]. Research is only beginning to investigate activity dosage in older medical patients with reports of: a reduced risk of 30-day hospital readmission above a threshold of 275 steps per day and further risk reduction for every 100 step increase in mean daily steps [16]; an increased risk of hospital associated functional decline if taking ≤900 steps per day [17,18] and the suggestion that walking at least twice a day for 20 min is associated with less functional decline in people of variable physical capabilities [19]. The problems of low mobility and SB in hospitals are complex because there are system issues, in addition to challenges relating to people, culture, the environment and operational processes [20].…”
Section: Introductionmentioning
confidence: 99%
“…The sedentary lifestyle that characterizes hospitalized older adults could contribute to the marked functional decline that they usually suffer, particularly during long hospital stays. Indeed, different studies have reported that hospitalised older adults spend most of the time in bed even when they are able to walk independently [31,32], with the levels of inactivity being related to the risk of HAD [10]. Increasing activity levels should therefore be a priority, especially in those patients with a better functional status at admission, with the latter theoretically allowing to maintain a more active lifestyle during the whole hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, although a number of factors can increase the risk of HAD [7][8][9], lack of physical activity during hospitalization seems particularly important. A recent study reported a mean daily non-sedentary time-that is, excluding sitting or lying in bed-of only one hour in hospitalized older adults, which in turn was associated with a greater HAD risk [10]. Strong evidence supports the beneficial role of in-hospital exercise programs to attenuate functional decline in older patients [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these include functional decline and increased frailty [ 2 ], resulting in hospital-acquired disability (HAD) [ 3 ]. One main reason for HAD is sedentary behaviour (SB) [ 4 ], which has been shown to result in increased loss of muscle mass and function [ 5 , 6 ]. The effects of SB during hospital admission persist post-discharge [ 7 ], with previously active older people more sedentary at home post-discharge as a result of HAD [ 8 ].…”
Section: Introductionmentioning
confidence: 99%